How intrinsic phonons manifest in infrared plasmonic resonances of crystalline lead nanowires - Vogt, Jochen; Hoang, Chung-Vu; Huck, Christian; Neubrech, Frank; Pucci, Annemarie (The journal of physical chemistry. C, Energy, materials, and catalysis, 2016)
Single-crystalline lead nanowires with length of about one micrometer and with effective diameters of a few tens of nanometers have been grown on vicinal silicon by a self-assembly process. They show strong plasmonic resonances in the infrared with a remarkable enhancement of the extinction upon the cooling below room temperature. The increase of the plasmonic extinction at resonance is linear with decreasing temperature but saturates before the Debye temperature is approached. This observation is in full accordance with the quasi-static description of plasmonic extinction with the intrinsic damping dominated by phonons and thus linearly temperature dependent well above the Debye temperature. The different slopes of this linear function for different wire thickness indicate the importance of surface and near surface phonon properties that can be described by a Debye temperature that is lower than the bulk value. The careful spectral analysis also yields temperature independent contributions to the electronic scattering rates for various wire thicknesses and, furthermore, a resonance frequency decreasing with temperature, which corresponds to the predicted trend in renormalization theory for electron-phonon interaction in a metal like lead.
Gesehen am 04.06.2020